A smart cane integrated with Artificial Intelligence (AI) capabilities / Farzana Bahrodin … [et al.] - Bahrodin, Farzana; Ahmad Nazri, Nurin Aqilah; Abdul Samat, Nurul Syafiqah; Norzali, Siti Aleeya Aisyah; Mohd Noor, Siti Umairah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Blind people sometimes have difficulty crossing pedestrian sidewalks because obstructions such as street sellers and motorcyclists obscure their guiding bricks. To solve this, we provide a revolutionary assistive technology: a smart cane equipped with AI capabilities. This innovation promises to improve navigation for visually impaired people by providing sophisticated features including an AI-powered GPS system with obstacle alerts, route recommendations, and real-time support. This smart cane, designed by Farzana Bahrodin, Nurin Aqilah Ahmad Nazri, Nurul Syafiqah Abdul Samat, Siti Aleeya Aisyah Norzali, Siti Umairah Mohd Noor, and lecturer Mr. Norazman Harun, detects objects within 50m and alerts users via sound and vibration. This idea significantly improves mobility and safety for the sight handicapped.